On twisted reality conditions - Tomasz Brzezinski (Letters in Mathematical Physics, 2019)
We study the twisted reality condition of Math. Phys. Anal. Geom. 19 (2016),no. 3, Art. 16, for spectral triples, in particular with respect to the product and the commutant.Motivated by this we present the procedure, which allows one to untwist the twisted spectraltriples studied in Lett. Math. Phys. 106 (2016), 1499–1530. We also relate this construction toconformally rescaled real twisted spectral triples, and discuss the untwisting of the ‘minimaltwist’ procedure of an even spectral triple.